Cytomegalovirus in Adult Allogeneic Blood and Marrow Transplant Patients Before or Around the Period of Neutrophil Recovery: A Single-Center, Retrospective, Descriptive Study. (9th March 2020) - Martin, Isabella; Valsamakis, Alexandra; Gladstone, Douglas; Jones, Richard; Ambinder, Richard; Avery, Robin K
Abstract: Background: Few reports exist on pre-engraftment cytomegalovirus (CMV) DNAemia in allogeneic blood or marrow transplant (allo BMT) recipients. We describe this clinical entity, its management, and the potential effect of 3 different quantitative CMV deoxyribonucleic acid (DNA) tests used during the 6-year study period. Methods: We performed a retrospective, single-center study of allo BMT recipients from 2010 to 2015 who developed CMV DNAemia before neutrophil recovery (absolute neutrophil count [ANC] <1000 cells/mm 3, "pre-engraftment CMV") or who became neutropenic concomitant with detectable CMV DNA ("peri-engraftment CMV"). Clinical data were collected from the electronic medical record. Results: Among 1151 adult allo BMT patients, 73 developed CMV DNAemia before engraftment or while neutropenic after initial engraftment. Most patients were eventually treated (valganciclovir or ganciclovir, N = 68; foscarnet, N = 1); 4 were not treated. First CMV detection occurred at median day +12 (range, 0–48), but treatment was not started until median day +33 (range, 4–105) at median ANC of 760 cells/mm 3 . Six patients had peak viral loads >5000 IU/mL; none had tissue-invasive disease. One developed ganciclovir resistance. No significant differences were observed upon stratification by quantitative CMV DNA test. Conclusions: Cytomegalovirus DNA was detected in 6.3% of pre- and peri-engraftment allo-HSCT patients. Ganciclovir derivatives were commonly used for treatment despite risk of neutropenia. Treatment was typically deferred until CMV DNA and ANC rose. With rare exceptions, this treatment strategy did not appear to have adverse clinical consequences with respect to acute CMV. Different CMV DNA quantification tests used performed similarly from a clinical perspective despite different analytical performance characteristics.